2022
DOI: 10.3389/fpsyg.2022.862965
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Home-Based Learning Experience During COVID-19 on Future Intentions to Study Online: A Chinese University Perspective

Abstract: As coronavirus disease 2019 (COVID-19) swept the world in early 2020, all the Chinese universities and colleges adopted online learning to fulfill the directive saying “classes suspended but learning continues.” Understanding the impact of this large-scale online learning experience on the future online learning intention of Chinese university students can help design better blended-learning activities. This study applies flow experience and theory of planned behavior (TPB) to construct a theoretical framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…During the COVID-19 pandemic, a shift to online learning was observed in many countries where modern information technology was used to deliver the learning contents initially planned for the classroom setting ( Zhao et al, 2022 ). Despite institutions’ efforts to ensure the continuity of education through online classes, the COVID-19 pandemic bore an academic impact on students, who were reported to be less motivated in learning and were experiencing dilemmas about the future of their careers ( Nell et al, 2020 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, a shift to online learning was observed in many countries where modern information technology was used to deliver the learning contents initially planned for the classroom setting ( Zhao et al, 2022 ). Despite institutions’ efforts to ensure the continuity of education through online classes, the COVID-19 pandemic bore an academic impact on students, who were reported to be less motivated in learning and were experiencing dilemmas about the future of their careers ( Nell et al, 2020 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…They specifically commented on their teachers’ lack of career orientation support. The context of the COVID-19 pandemic thrust the world into the first large-scale online learning experiment ( Zhao et al, 2022 ), with no prior conception of how the interaction in the online learning context should be carried out. The qualitative results of Price et al (2007) study indicated that students’ and their tutors’ conceptions of their roles in an online environment need to be addressed to achieve effective online communication and interaction.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The use of MOOCS for corporate training fits well with the current disruption in the education system due to Covid-19 and the evolving Fourth Industrial Revolution (4IR). The Covid-19 pandemic, coupled with the ongoing digitization due to the 4IR, has provided an opportunity to reflect and recalibrate teaching and learning for the support of a resilient education system in all sectors worldwide (Kanwar & Daniel, 2020;Zhao, Ao, Wang, & Wang, 2022). Besides that knowledge and societies advance during an industrial revolution, 4IR…”
Section: Massive Open Online Courses For Scalability and Transformati...mentioning
confidence: 99%
“…Importantly, MOOCs are supported by accredited universities and experts in the field (Zhao et al, 2022). MOOCs can be tailored to fit the needs of an organization.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Another basis for the discussion of this theory the authors highlighted in the study was that Web-based learning, also known as e-learning programs, had been designed to include groups of learners. These include working adults who are unable to attend face-to-face classes, isolated communities far from institutions, economically disadvantaged people, and undergraduate students who need to attend classes spontaneously (Picciano, 2017;Zhao et al, 2022). This understanding made the discussion of technology application in learning, together with the pedagogies involved, important factors in MOOCs implementation.…”
Section: Theoretical Foundationsmentioning
confidence: 99%